Lanskap Hukum Australia Mengenai Donasi Mitokondria - Grace Lendawati Amelia Turalaki (Syntax Idea)
Mitochondrial donation is an assisted reproductive technology used to minimize the risk of transmitting serious mitochondrial diseases from mother to child. The aim of this research is to examine the Australian legal landscape regarding mitochondrial donation. This research uses a literature review research method. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The results show that Western Australian legislation (external site) currently prohibits the use of embryos containing the genetic material of more than two people, and this is one of the reasons why mitochondrial donation is not currently legal in Western Australia. In 2021, following a Senate Committee Review and Community Consultation, the Commonwealth Government introduced the Mitochondrial Donation Law Reform Bill (Maeve's Law) (2021) which proposes a phased approach to amending Commonwealth laws that currently make mitochondrial donation illegal. The bill was passed on 30 March 2022. Assisted reproductive technology legislation is under review in Western Australia and the Western Australian Government has committed to engaging in national consultation on new technologies, including mitochondrial donation.